Biphoton entanglement of topologically distinct modes - Doyle, Cooper; Zhang, Wei Wei; Wang, Michelle; Bell, Bryn A.; Bartlett, Stephen D.; Blanco-Redondo, Andrea (Physical Review A, 2022)
The robust generation and manipulation of entangled multiphoton states on chip has an essential role in quantum computation and communication. Lattice topology has emerged as a means of protecting photonic states from disorder, but entanglement across different topologies remains unexplored. We report biphoton entanglement between topologically distinct spatial modes in a bipartite array of silicon waveguides. The results highlight topology as an additional degree of freedom for entanglement and open avenues for investigating information teleportation between trivial and topological modes.
CRIS-Team Scopus Importer:2022-03-18